Outline of Field Observations during 1995 - 1996(Glaciological Data Collected by the 36th Japanese Antarctic Research Expedition during 1995 - 1996) - AZUMA, Nobuhiko; KAMEDA, Takao; NAKAYAMA, Yoshiki; TANAKA, Yoichi; YOSHIMI, Hideshi; FURUKAWA, Teruo; AGETA, Yutaka
application/pdf application/pdf journal article